Kebijakan Rekonstruksi Pengaturan Hakim Pemeriksa Pendahuluan dalam Kitab Undang-Undang Hukum Acara Pidana Tahun 2015 - Dwi Nurahman (Law Faculty of Universitas Bandar Lampung, 2015)
Pre-trial has been set in the Criminal Procedure Code reap a lot of criticism from legal practitioners. In practice, it turns out pre-trial failed to give justice to those seeking justice in particular suspects in criminal proceedings. Government and Parliament have made a Draft Law on the Code of Criminal Procedure (Draft Criminal Code) which one to replace it with a Justice Pre Preliminary Examining Judge. The main problem in implementing this research include: What is the reason for that is the basis for the reconstruction policy settings Preliminary Examining Judge in Criminal Procedure Bill 2015. Results of this study are: the reason on which to base the reconstruction policy settings Preliminary Examining Judge is to better protect human rights guarantees in particular for seeking justice in the criminal justice process.